WHAT DIPLOMATS DO : The Life and Work of Diplomats - Barder, Brian (Rowman & Littlefield, 2014)
What do diplomats actually do? That is what this text seeks to answer by describing the various stages of a typical diplomat’s career. The book follows a fictional diplomat from his application to join the national diplomatic service through different postings at home and overseas, culminating with his appointment as ambassador and retirement. Each chapter contains case studies, based on the author’s thirty year experience as a diplomat, Ambassador, and High Commissioner. These illustrate such key issues as the role of the diplomat during emergency crises or working as part of a national delegation to a permanent conference as the United Nations. Rigorously academic in its coverage yet extremely lively and engaging, this unique work will serve as a primer to any students and junior diplomats wishing to grasp what the practice of diplomacy is actually like.